2018
DOI: 10.2478/johr-2018-0004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Apple Seed Stratification with Growth Regulators on Breaking the Dormancy of Seeds, the Growth of Seedlings and Chlorophyll Fluorescence

Abstract: The aim of the study was to shorten the period of breaking dormancy in apple seeds and to improve the growth of the seedlings of 'Gold Milenium', 'Ligol' and 'Szampion'. The whole seeds were removed from fruits directly after the harvest and were subjected to stratification (3 °C for 90 days in darkness) in distilled water or an aqueous solutions of 500 mM salicylic acid (SA), 10 -3 M jasmonic acid (JA), gibberellin A3 (GA3) and 6-benzylaminopurine (BAP) at 250 mg·dm -3 and 100 mg·dm -3 , respectively. Growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Although it has been observed that Moist Chilling inhibits both the percentage and rate of germination in S. leptoclada (PEREZ-GARCIA and GONZALEZ-BENITO, 2006;VELDHUIZEN and KNIGHT, 2006), we found that both Moist Chilling and scarification by 0.2% potassium nitrate can cause a high percentage of germination in the initial days of incubation. Similar results were reported in previous studies for the species of Foeniculum vulgar L. (SOLTANIPOOR et al, 2009), Allyssum homalocarpum (GANJALI and AJORLO, 2014), Teucrium polium (KOOCHAKI and AZIZI, 2005), Stevia rebaudiana (LIOPA-TSAKALIDI et al, 2012), Citrullus colocynthis (SABERI et al, 2011), walnut (QURESHI et al, 2016, Phoenix dactylifera L. (MUHAMMAD et al, 2017), Brassica tournefortii (MAHAJAN et al, 2018), Kiwifruit (ZHANG et al, 2018, Elaeocarpus serratus L. (RAJI and SIRIL, 2018), Rice seed (SHIRATSUCHI et al, 2017), Apple seed (GORNIK et al, 2018), Pistacia khinjuk (ACAR et al, 2017;JIA et al 2020;BI et al 2021) and Sterculia urens Roxb (SUBNASHINI-DEVI et al, 2012;SI et al, 2020;).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been observed that Moist Chilling inhibits both the percentage and rate of germination in S. leptoclada (PEREZ-GARCIA and GONZALEZ-BENITO, 2006;VELDHUIZEN and KNIGHT, 2006), we found that both Moist Chilling and scarification by 0.2% potassium nitrate can cause a high percentage of germination in the initial days of incubation. Similar results were reported in previous studies for the species of Foeniculum vulgar L. (SOLTANIPOOR et al, 2009), Allyssum homalocarpum (GANJALI and AJORLO, 2014), Teucrium polium (KOOCHAKI and AZIZI, 2005), Stevia rebaudiana (LIOPA-TSAKALIDI et al, 2012), Citrullus colocynthis (SABERI et al, 2011), walnut (QURESHI et al, 2016, Phoenix dactylifera L. (MUHAMMAD et al, 2017), Brassica tournefortii (MAHAJAN et al, 2018), Kiwifruit (ZHANG et al, 2018, Elaeocarpus serratus L. (RAJI and SIRIL, 2018), Rice seed (SHIRATSUCHI et al, 2017), Apple seed (GORNIK et al, 2018), Pistacia khinjuk (ACAR et al, 2017;JIA et al 2020;BI et al 2021) and Sterculia urens Roxb (SUBNASHINI-DEVI et al, 2012;SI et al, 2020;).…”
Section: Discussionmentioning
confidence: 99%
“…The presented results also show that "Balady Variety (Amar)" and "Hamawy" variety varied in their stratification requirements. In this respect, 29 reported that apple seed germination relied on the varities and also the manner of stratification. Among the examined cultivars, 'Szampion' seeds germinated at the very best share.…”
Section: Discussionmentioning
confidence: 99%
“…The presented results also show that apricot seedling trees varied in their stratification requirements. In this respect, [45] reported that apple seed germination depended on the cultivar and the manner of stratification. Among the examined cultivars, 'Szampion' seeds germinated at the highest percentage.…”
Section: Jhpr Volume 14mentioning
confidence: 99%